Uji kepekaan antibiotik kanamisin terhadap isolat klinis Mycobacterium tuberculosis menggunakan metode mycobacterium growth indicator tube (MGIT) 960 - Triawan, Agung Nicky; Sulfiani; Subair (Program Studi Teknologi Laboratorium Medis, 2024)
Tuberculosis (TB) is an infectious disease that is a major cause of ill health and one of the main causes of death throughout the world. TB is caused by Mycobacterium tuberculosis, this disease usually attacks the lumgs but it can also attack other parts of the body. Kanamycin is one of the main second-line drugs for the traetment of tuberculosis. The patients suffering from tuberculosis are caused by multing-resistent strains with resistence to anti-tuberculosis drugs. Kanamycin is an aminoglycoside antibiotic that works to inhibit the protein synthesis process of microorganisms. This research aimed to determine the sensitivity of the antibiotic kanamycin to clinical isolates of TB by using the Mycobacterium Growth Indicator Tube (MGIT) 960 method. The type of reaserch used descriptive with an experimental method which aimed to test the sensitivity of the antibiotic kanamycin to clinical isolates of Mycobacterium Growth Indicator Tube (MGIT) 960. From the results of reaserch conducted on 20 (100%) samples, 4 (20%) samplesm were resistent, and 16 (18%) samples sensitive. This proves that the antibiotic kanamycin is stil suitable for use because the examinations results obtained showed that the antibiotic was still sensitive in some respondents who used the amtibiotic.